2022
DOI: 10.1111/all.15610
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of immediate reactions to amoxicillin: Comparison of basophil activation markers CD63 and CD203c in a prospective study

Abstract: BackgroundAmoxicillin (AX) combined or not with clavulanic acid (CLV) is frequently involved in IgE‐mediated reactions. Drug provocation test (DPT) is considered as the gold standard for diagnosis, although contraindicated in high‐risk patients. Basophil activation test (BAT) can help diagnose immediate reactions to beta‐lactams, although controversy exists regarding the best activation marker. We have performed a real‐life study in a prospective cohort to analyze the real value of BAT as diagnostic tool and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
(86 reference statements)
2
9
0
Order By: Relevance
“…and CD203c, in a prospective evaluation of amoxicillin (AX) and CLV allergic patients showed that the best sensitivity and specificity was obtained for CD203c (46.6% and 94.6%), with good positive predictive value and like-hood ratio. 43 These results are in line with those obtained by Abuaf et al 44 However, another recent study in IDHRs to AX obtained lower sensitivity (23%) when selecting a high specificity (95%). 45 All this suggests that methodological or analytical variations in the classical procedure could be useful to improve the diagnostic value of BAT.…”
Section: Identification Of Ige-mediated Idhrs Is Mainly Based On Skin...supporting
confidence: 87%
“…and CD203c, in a prospective evaluation of amoxicillin (AX) and CLV allergic patients showed that the best sensitivity and specificity was obtained for CD203c (46.6% and 94.6%), with good positive predictive value and like-hood ratio. 43 These results are in line with those obtained by Abuaf et al 44 However, another recent study in IDHRs to AX obtained lower sensitivity (23%) when selecting a high specificity (95%). 45 All this suggests that methodological or analytical variations in the classical procedure could be useful to improve the diagnostic value of BAT.…”
Section: Identification Of Ige-mediated Idhrs Is Mainly Based On Skin...supporting
confidence: 87%
“…Finally, we thank the authors for the figure S2 observation. 2 Certainly, part A does not correspond to individual results, it has beenamistakeandtherepresentationcorrespondstoSIresultsin-stead%results.ThecorrectgraphisshowninFigure 1B.…”
mentioning
confidence: 71%
“…We read the paper by Céspedes et al 1 with interest. However, we respectfully disagree with their generalizing proposal placing the basophil activation test (BAT) as a primary diagnostic in the diagnostic algorithm to document immediate hypersensitivity to amoxicillin.…”
mentioning
confidence: 99%
“…From the literature, it has emerged that 90% of “penicillin‐allergic” patients tolerate the alleged culprit(s) 6–9 . However, the authors 1 document an immediate allergy to amoxicillin (AX) or clavulanic acid in 66% of their patients. This likely relates to their study population.…”
mentioning
confidence: 99%
See 1 more Smart Citation